Application of the Equivalence Scales to Poverty Measurement - Rusnak, Zofia (Zastosowanie skal ekwiwalentności do pomiaru ubóstwa, 2007)
There are 2 basic aims of this paper. The first one is to define, to what extent the choice of equivalence scale implies the shape and parameters of income and expenditure distribution in households of different demographic profiles. The second one is an attempt to estimation of changes in the extent and the depth of poverty of chosen household types, caused by the choice of different equivalence scales. In poverty analysis two normative scales were used: original and modified OECD scale.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1162, s. 162-178